(untitled) (Journal of Parents and Teachers, 2016)
Everything will happen in the future, it takes place before throughout the school. The next Pace’s Prize Novel, the investigators who discover a vaccination against to the cancer, the engineers who build the first solar car, the politicians who develop other formulas of representation, the biggest revolutionaries of films, mode and Art, the visionaries and the avant-gardes, all of them learn in a today’s school. While we share these words, the seeds of a future doctor, lawyer, astronaut, leader, journalist, writer… it brings up in a boy and girl, it is promoted by its teachers and its school. Because, the school has the unique ability to predict the future by creating it.